2012
DOI: 10.1161/circinterventions.112.971291
|View full text |Cite|
|
Sign up to set email alerts
|

Blood Transfusion and the Risk of Acute Kidney Injury After Transcatheter Aortic Valve Implantation

Abstract: Background-Blood transfusion is associated with acute kidney injury (AKI) after transcatheter aortic valve implantation (TAVI). We sought to elucidate in more detail the relation between blood transfusion and AKI and its effects on short-and long-term mortality. Methods and Results-Nine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
86
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 37 publications
(61 reference statements)
9
86
3
Order By: Relevance
“…In this study, the possibility of heterogeneity in timing of the collection of data in each institution precluded an accurate estimation of the total blood loss calculated by the Landefeld equation (which assumes that the net Hb decline corresponds to the addition of the number of blood transfusion to the baseline minus measured postoperative nadir Hb). 31 Yet, in accordance with our previous findings, 32 the current results show that patients with anemia had a smaller postoperative Hb drop but received significantly more frequent and also more units of blood transfusions compared with patients without anemia ( Figure 3). Also, the indication of blood transfusion was not related to an overt source of bleeding in ≈60% of patients with anemia.…”
Section: Prognostic Effects Of Preoperative Anemia and Blood Transfussupporting
confidence: 92%
“…In this study, the possibility of heterogeneity in timing of the collection of data in each institution precluded an accurate estimation of the total blood loss calculated by the Landefeld equation (which assumes that the net Hb decline corresponds to the addition of the number of blood transfusion to the baseline minus measured postoperative nadir Hb). 31 Yet, in accordance with our previous findings, 32 the current results show that patients with anemia had a smaller postoperative Hb drop but received significantly more frequent and also more units of blood transfusions compared with patients without anemia ( Figure 3). Also, the indication of blood transfusion was not related to an overt source of bleeding in ≈60% of patients with anemia.…”
Section: Prognostic Effects Of Preoperative Anemia and Blood Transfussupporting
confidence: 92%
“…Elhimidi et al [43] demonstrated pre-procedural serum creatinine level to be a predictor of AKI (OR [95% CI] 3.7 (1.24-11.3); p = 0.019) as did Khawaja et al [44] (OR [95% CI] 1.57 (1.11-2.21); p = 0.010) who also, like our study found pre-existing diabetes to strongly predict AKI. Other series however have not found an association between baseline renal function or the presence of CKD and AKI development after TAVI [29,41,45,46]. Post-operative red blood cell (RBC) transfusion has been strongly implicated in the literature as an independent predictor of AKI following TAVI [39,41,[46][47][48][49][50] but did not reach statistical significance in our multivariate model.…”
Section: Acute Kidney Injury Following Tavicontrasting
confidence: 56%
“…Other series however have not found an association between baseline renal function or the presence of CKD and AKI development after TAVI [29,41,45,46]. Post-operative red blood cell (RBC) transfusion has been strongly implicated in the literature as an independent predictor of AKI following TAVI [39,41,[46][47][48][49][50] but did not reach statistical significance in our multivariate model. Only six (5.3%) patients required post-operative RBC transfusion overall and although a greater proportion belonged to the group who did develop AKI compared to those who did not (12.5% vs. 3.3%, p = 0.107, Supplementary Table 4) this was not a statistically significant difference and was therefore likely underpowered in our model.…”
Section: Acute Kidney Injury Following Tavicontrasting
confidence: 56%
See 1 more Smart Citation
“…Karkouti (144) identified 20 observational studies showing an association between transfusion of packed red blood cells and AKI (and 1 study that found no difference). Since that time, additional studies have added to the growing body of literature suggesting that anemia and the use of packed red blood cells are independent risk factors for AKI after cardiac surgery (145)(146)(147). Catalytic iron (i.e., circulating iron not bound to any proteins) can produce hydroxyl radicals, cause oxidative tissue damage, and has been proposed as a nephrotoxin (148).…”
Section: Perioperative Transfusion Of Packed Red Blood Cellsmentioning
confidence: 99%